Homeopathic Modulation to Optimize Scalp Intelligence in Dandruff Management (Homoeopathy for All, 2026)
About 30–50% of adults globally suffer with dandruff. Traditionally considered a benign cosmetic issue related to poor hygiene or dry scalp, dandruff is now recognized as a scalp biology condition including inflammation, epidermal barrier malfunction, and microbial imbalance., Its recurrent nature, frequent relapse after symptomatic treatment, and association with pruritus, erythema, hairfall and psychological distress highlight that dandruff represents more than superficial flaking. Modern research views dandruff as a multifaceted pathophysiological process involving the scalp as an active, sensitive biological unit. A rich network of sebaceous glands, immunological cells, nerve endings, and a complex microbiome allows the scalp to sense and respond dynamically to internal and external stimuli. Epidermal homeostasis depends on this regulatory capacity, called “scalp intelligence”. Its disparity can cause accelerated keratinocyte turnover, altered sebum composition, and low-grade inflammation manifested clinically as dandruff.
Keywords: pathophysiological process; scalp intelligence; Dysregulation; hormonal fluctuations